2019
DOI: 10.1089/lap.2019.0219
|View full text |Cite
|
Sign up to set email alerts
|

Motivations of Males with Severe Obesity, Who Pursue Medical Weight Management or Bariatric Surgery

Abstract: Background: Both medical weight management (MWM) and bariatric surgery are significantly underutilized by patients with severe obesity, particularly males. Less than 30% of participants in MWM programs are male, and only 20% of patients undergoing bariatric surgery are men. Objectives: To identify motivations of males who pursue either MWM or bariatric surgery. Setting: Interviews with males with severe obesity (body mass index q35 kg/m 2), who participated in a Veteran Affairs weight loss program in the Midwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…It refers to a person's perception of the effectiveness of various actions available to reduce the threat of illness. Able to perceive the treatment may improve physical and psychological health, enhance the quality of life, and be sure about the health state may facilitate health-seeking behaviour among men (Jahangir et al, 2020;Jolles et al, 2019).…”
Section: Perceived Benefitmentioning
confidence: 99%
“…It refers to a person's perception of the effectiveness of various actions available to reduce the threat of illness. Able to perceive the treatment may improve physical and psychological health, enhance the quality of life, and be sure about the health state may facilitate health-seeking behaviour among men (Jahangir et al, 2020;Jolles et al, 2019).…”
Section: Perceived Benefitmentioning
confidence: 99%
“…Targeting bariatric surgery candidates with a BMI equal to or higher than 40 kg/m 2 may be a challenge when it comes to recruitment. Even so, this type of participant is often motivated and willing to participate, to have the opportunity to improve health, optimize quality of life, and lengthen lifespan [ 58 , 59 ]. Previous studies have reported that changes in body weight beginning at 2–5% can bring improvements in several associated risk factors [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…VHA providers included primary care providers [PCPs], bariatric surgeons, dietitians, and health psychologists. We have published the interview guides, study procedures and findings previously [ 18 , 20 ]. Themes that were pertinent to each IMB domain (e.g., Veteran motivations for achieving weight loss) were incorporated into a transcript that was written for the TOTAL video.…”
Section: Methodsmentioning
confidence: 99%